The Concept of the Global Hunger Index - von Grebmer, Klaus; Bernstein, Jill; Nabarro, David; Prasai, Nilam; Amin, Shazia; Yohannes, Yisehac; Sonntag, Andrea; Patterson, Fraser; Towey, Olive; Thompson, Jennifer (Welthungerhilfe, 2016)
The Global Hunger Index (GHI) is a tool designed to comprehensively measure and track hunger at the global, regional, and country levels.1 The International Food Policy Research Institute (IFPRI) calculates GHI scores each year to assess progress, or the lack thereof, in combating hunger. The GHI is designed to raise awareness and understanding of the struggle against hunger. By calling attention to the issue, we hope that this report will help to increase the commitment and resources dedicated to ending hunger worldwide. All 17 Sustainable Development Goals (SDGs)—including Goal 2, ending hunger, achieving food security and improved nutrition, and promoting sustainable agriculture—should be achieved by 2030. Other global initiatives, like Compact2025, have set the goal of ending hunger worldwide by 2025. Yet this cannot be achieved without increased effort and mobilization of resources. We believe there is truth to the adage that “what gets measured gets done”; thus, we intend to consistently and systematically measure global hunger to help ensure that it will be eradicated quickly and once and for all.